2008
DOI: 10.1111/j.1365-294x.2008.03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive polymorphism and geographical variation at a positively selected MHC class II B gene of the lesser kestrel (Falco naumanni)

Abstract: Understanding the selective forces that shape genetic variation in natural populations remains a high priority in evolutionary biology. Genes at the major histocompatibility complex (MHC) have become excellent models for the investigation of adaptive variation and natural selection because of their crucial role in fighting off pathogens. Here we present one of the first data sets examining patterns of MHC variation in wild populations of a bird of prey, the lesser kestrel, Falco naumanni. We report extensive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(150 citation statements)
references
References 90 publications
(155 reference statements)
6
143
1
Order By: Relevance
“…Temporal shifts of selection, affected by temporal changes in prey availability or prey preference, may also have led to patterns of variation that we detected. In some taxa, patterns of variation at MHC genes are substantially different from those of neutral loci [71,72]. For example, differentiation of MHC loci among populations of grey seals is associated with habitat differences [71].…”
Section: (B) Geographical Variation In Dietmentioning
confidence: 99%
“…Temporal shifts of selection, affected by temporal changes in prey availability or prey preference, may also have led to patterns of variation that we detected. In some taxa, patterns of variation at MHC genes are substantially different from those of neutral loci [71,72]. For example, differentiation of MHC loci among populations of grey seals is associated with habitat differences [71].…”
Section: (B) Geographical Variation In Dietmentioning
confidence: 99%
“…Positive colonies were amplified using universal M13 forward and reverse primers (M13F: 5 0 -GTAAAACGAC-GGCCAG-3 0 ; M13R: 5 0 -CAGGAAACAGCTATGAC-3 0 ) and 6-8 clones per individual were randomly selected for sequence analysis. Following the standards described in Alcaide et al (2008), rare cloned sequences found only once and differing by o3 bp from a redundant sequence of the same PCR product were considered as PCR artifacts and assumed to have been sampled already. As recombination of cloned PCR products can result in additional artifacts, comparisons were conducted between cloned sequences and direct sequencing of uncloned PCR products to get reliable polymorphic sites.…”
Section: Amplification and Sequencingmentioning
confidence: 99%
“…The exon and intron boundaries were defined following the annotated genes in the reference saker genome. In addition, we analyzed exonic variation in two well-characterized gene systems with known exonic variations in vertebrates linked to phenotypic diversity and pathogen resistance, the melanocortin-1-receptor (MC1R; Zhan et al, 2012) and major histocompatibility complex (MHC) Class II B (Alcaide et al, 2008).…”
Section: Contrasting Roles Of Exonic and Intronic Snps X Zhan Et Almentioning
confidence: 99%
“…Southern hybridization methods have been used to estimate the number of genes and alleles/locus for the class I and II loci thereby providing a rough estimate of overall genetic variation at the MHC (Emara et al, 1992;Westerdahl et al, 2000;Freeman-Gallant et al, 2002;Richardson and Westerdahl, 2003;Alcaide et al, 2008). PCR-based techniques such as reference strand-mediated conformational analysis, single strand conformation polymorphism and denaturing gradient gel electrophoresis (DGGE) are also effective in estimating the number of alleles, especially when locus-specific primers are available (Ramon et al, 1998;Goto et al, 2002;Westerdahl et al, 2004;Knapp, 2005;Alcaide et al, 2010).…”
Section: Introductionmentioning
confidence: 99%